Avaliação de parâmetros que afetam a produção de energia elétrica em um sistema fotovoltaico em propriedade rural - Ramanauskas, Luiza Ferreira da Costa (2019)
Photovoltaic (PV) systems installed in rural areas are becoming a reality in Brazil to reduce production costs involved in this activity. The objective of this work is to analyze parameters that affect the output power of a 20 kWp on-grid photovoltaic systems connected to the low voltage installed in rural property associated with the agroindustrial cooperative in the municipality of Assis Chateaubriand, and the activity is the poultry production. It was determined that PV system array would be installed on the roof of the aviary with orientation of the roof. By characterizing the crystalline silicon PV modules, the average value of the power of the 60 devices was 1.9 % higher than the value presented by the manufacturer datasheet, which is 340 W. The PV system consists of four panels with 15 modules each, associated in series. The total installed power was 20.8 kWp. The maximum output power ranged from 17 kW to 15 kW and 11 kW at solar noon on a clear day near the summer solstice, autumnal equinox and winter solstice. The inverter presented problems that reduced the output AC power, in the day next to the equinox, when the aviary was in production period. For a period with similar solar irradiance and greater than 540 W/m², there is a reduction of the temperature of the PV modules of 2.6 ºC with the increase of the wind speed of 1 m/s.The electrical energy in the month of June was of around 30 % and 50 % less than the electrical energy produced in March and December, respectively. The highest daily value of performance ratio was 86 % and occurred in days in the summer and winter months and is equal to the simulated value. The monthly yield was 160 kWh/kW, 113 kWh/kW and 81 kWh/kW for the summer, autumn and winter months, respectively. The estimated payback for the PV system is 8 years.